Social Media-Based Marketing Strategies in Volleyball: A Contemporary Literature Review - Sahabuddin, Sahabuddin; Hamid, Muflih Wahid (Journal of Sport Education, Coaching, and Health (JOCCA), 2025)
This study aims to present a systematic literature review on social media-based marketing strategies in volleyball during the 2015–2025 period. Twenty-three articles obtained from Scopus, Google Scholar, Web of Science, DOAJ, SINTA, and Garuda databases were analyzed using thematic analysis and narrative synthesis techniques. The results indicate that social media has become a key element in modern sports marketing, particularly through platforms like Instagram, TikTok, and YouTube. Visual content such as highlight videos, behind-the-scenes videos, and athlete storytelling have proven to be the most effective strategies in increasing engagement and brand awareness. Furthermore, direct interaction between athletes and fans through live chat, comments, and Q&A features significantly contributes to audience loyalty and retention. The analysis also found that the use of social media analytics plays a crucial role in developing a more targeted digital marketing strategy. Clubs or athletes that actively monitor digital metrics such as engagement rate, reach, and impressions tend to have better marketing performance. Despite its significant potential, implementing digital strategies still faces challenges such as a lack of media professionals, content consistency, and unequal access to technology. Overall, the review results indicate that social media-based marketing strategies have a significant impact on the development of the volleyball industry. Further research is recommended to develop an integrated digital strategy model that sports organizations can use to improve their competitiveness and marketing performance.